Influence of Displacement Ductility on Concrete Contribution to Shear Strength - Guray, Arslan; Izzet, Kiristioglu (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2016)
Shear strength of reinforced concrete (RC) members is composed of the contributions of the nominal shear strength provided by transverse reinforcement and concrete. The shear strength of RC members under cyclic lateral loading degrades much faster than the flexural strength. Based on this state, Seismic Codes tend to be excessively conservative and do not take into account the contribution of concrete in certain cases. The aim of this study is to investigate the influence of displacement ductility on concrete contribution to shear strength using finite element analyses (FEA). Based on the agreement between the FEA and experimental results selected from literature, a simple relation is proposed for the prediction of the concrete contribution to shear strength of RC beams. The relation proposed takes into account a reduction of the normalized concrete contribution for increasing inelastic displacement demands, with a small residual strength at large ductility levels.
Keywords: reinforced concrete; beam; shear strength; displacement ductility; RC BEAMS; COLUMNS; MODEL; DEGRADATION; CAPACITY; Engineering